Piezoresistance and Electrical Conduction in Solution-Processed 2D Nanosheet Networks - Caffrey, Eoin (Trinity College Dublin. School of Physics. Discipline of Physics, 2025)
Nanosheet networks are attracting much interest as printed electronic devices, utilising the physical properties of 2D nanosheets. Electrical conduction and the impact of strain on conduction in the networks is of particular interest when considering applications as wearable devices, for measuring strain or as flexible electronics and interconnects. As nanosheet networks become thinner, they enter a percolation regime, where the electrical conductivity is no longer an intrinsic material property. In this study, networks of liquid phase exfoliated (LPE) graphene nanosheets were spray coated onto flexible polymer substrates. The unstrained electrical conductivity of the networks was measured, and the networks were strained linearly and with cyclic profiles. Both conductivity and piezoresistance show percolative behaviours for thinner networks. They transition to bulk-like behaviour when the network thickness is greater than ~100 nm. This data yielded a bulk conductivity of ~260 S/m. Using percolation theory, an equation for the gauge factor as a function of network thickness and network conductivity in the percolation region was derived. These models describe the experimental data very well, including the divergence in the gauge factor as the percolation threshold is approached from above. They also show that the dominant factor contributing to the piezoresistive response in the percolation regime is the effect of strain on the network structure. These networks have a maximum gauge factor of ~350, close to the percolation threshold, while having stable cyclic responses, with minimal electrical hysteresis and a minimal frequency dependence on the piezoresistive response. As network resistivity has been shown to depend on nanosheet dimensions, it was hypothesised that a similar effect may apply to the piezoresistive response. LPE graphene nanosheets were size selected using liquid cascade centrifugation to produce inks with six distinct nanosheet thickness distributions ranging from ~20 nm to ~3 nm. These were spray coated onto flexible substrates and tested electrically, and the piezoresistive response of each was extracted from cyclic strain measurements. The network resistivity decreased with decreasing nanosheet thickness, in line with existing models, however the gauge factor increased with increasing nanosheet thickness. Using an existing model, the nanosheet resistivity and junction resistances were determined to be (2.9 ± 1.3) ×10-5 Ωm and 8.9 ± 1.0 kΩ respectively. To understand the change in gauge factor, this model was used as a starting point to derive a new model relating gauge factor to nanosheet thickness. Fitting the model enabled the effect of strain on the nanosheets and the inter- nanosheet junctions to be differentiated. In this system, the fitting suggests that the graphene nanosheets have a negative piezoresistive response. Changing the nanosheet aspect ratio can have a significant impact on the electrical performance of devices made from nanosheet networks. Inks of LPE and electrochemically exfoliated (EE) nanosheets were prepared and spray coated to form films. The network structure of both materials was characterised using nanotomography, which illustrated the increased conformality and reduced porosity of EE networks. The bulk electrical conductivity of the networks differed by an order of magnitude, with the EE network being more conductive. Both networks displayed percolation behaviour in the conductivity as a function of network thickness. Fitting these with a percolation model yielded scaling exponents in line with the 2D and 3D exponents for EE and LPE networks respectively. The piezoresistive response of the LPE networks was higher in the bulk regime, however both materials showed an increase in piezoresistance as the percolation threshold thickness was approached from above. These changes can be understood with respect to the network structure and the nanosheet sizes. Novel impedance spectroscopy techniques are enabling the direct measurement of nanosheet resistance and junction resistance in 2D nanosheet networks, offering a potential avenue to further mechanistic understanding of the piezoresistive effect in nanomaterial systems. Networks of EE MoS2 were characterised electromechanically using both DC resistance and AC impedance spectroscopic techniques. DC piezoresistance showed a relatively low gauge factor of ~3, with a linear response which withstood cyclic deformation. The AC impedance measurements showed that the junction resistance increased linearly with strain while the nanosheet resistance remained constant. These observations are consistent with highly aligned nanosheets sliding past one another under the application of strain, without transferring strain to the nanosheets themselves. This technique may enable further mechanistic insight into a range of piezoresistive nanomaterial systems.
APPROVED
Keywords: Graphene; Piezoresistance; Conduction; Solution Processing; Printed Devices; Strain; 2D Materials; MoS2; Liquid Phase Exfoliation; Electrochemical Exfoliation; Gauge Factor; Nanosheets; Nanosheet Networks; Junctions; Strain Sensor; Flexible Electronics